Animal welfare – a new term in kazakhstan’s legislation (Journal of actual problems of jurisprudence, 2021)
Over the past several decades the term “animal welfare” has been introduced into the legislation of many countries around the world. More and more citizens are realizing the importance of responsible treatment of animals and the impact of animal welfare on human daily life: on the quality of agricultural products, public health and climate. In the legislation of Kazakhstan the term “animal welfare” has also begun to be gradually introduced into the texts of various regulations, but the legislative definition of this term is still missing. Often the meaning of this term often is not clear for the law enforcement authorities. The objectives of this study are to analyze the origin and meaning of this term; substantiation of the importance of the institution of animal welfare, as well as the identification of Kazakhstani normative acts in which this term is used. In the study, we analyzed all Kazakhstan’s normative acts containing this term, as well as significant for Kazakhstan international documents that also use it. Despite the obvious importance of this study and its relevance in the context of a pandemic and an increase in world trade, this article is the first in Kazakhstani legal science to address the problem of legislative regulation of animal welfare. The article concludes with the recommendations for improving Kazakhstani legislation in the field of animal management, which constitutes the practical applicability of this work.Keywords: animal welfare, public health, treatment of animals.